Analisis Pengaruh Posisi Fairlead Terhadap Rasio Kerusakan Akibat Kelelahan Pada Struktur Tali Tambat Tipe Catenary FPSO Aoka Mizu - Nur Indah; Fuad Mahfud Assidiq (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
This research discusses the effect of fairlead position on the fatigue damage ratio of the Aoka Mizu Floating Production Storage and Offloading (FPSO) catenary structure during moored conditions. The FPSO is subject to the influence of ocean waves, ocean currents, and wind that can cause significant movement, jeopardize the catenary mooring system, and disrupt the production process. This study utilizes a numerical method based on the Boundary Element Method and uses environmental data from the Masela Block, which includes wave, wind, and current data. Three variations of fairlead position (0.3T, 0.5T, and 0.9T), each referring to the fairlead distance from the laden to the ship's keel, were tested with a rope length of 3100 m and a sea depth of 1000 m. The results showed that a fairlead position of 0.3T resulted in low stress and damage levels, while fairlead positions of 0.5T and 0.9T resulted in higher stress and damage. The fairlead position plays an important role in determining the stability and performance of the FPSO catenary structure. A fairlead position of 0.3T appears to be the most favorable option to reduce the risk of damage and stress to the FPSO Aoka Mizu catenary mooring system during moored conditions.